Telomeric Repeats Facilitate CENP-A(Cnp1) Incorporation via Telomere Binding Proteins - Castillo, Araceli G. (Public Library of Science, 2013)
The histone H3 variant, CENP-A, is normally assembled upon canonical centromeric sequences, but there is no apparent obligate coupling of sequence and assembly, suggesting that centromere location can be epigenetically determined. To explore the tolerances and constraints on CENP-A deposition we investigated whether certain locations are favoured when additional CENP-A(Cnp1) is present in fission yeast cells. Our analyses show that additional CENP-A(Cnp1) accumulates within and close to heterochromatic centromeric outer repeats, and over regions adjacent to rDNA and telomeres. The use of minichromosome derivatives with unique DNA sequences internal to chromosome ends shows that telomeres are sufficient to direct CENP-A(Cnp1) deposition. However, chromosome ends are not required as CENP-A(Cnp1) deposition also occurs at telomere repeats inserted at an internal locus and correlates with the presence of H3K9 methylation near these repeats. The Ccq1 protein, which is known to bind telomere repeats and recruit telomerase, was found to be required to induce H3K9 methylation and thus promote the incorporation of CENP-A(Cnp1) near telomere repeats. These analyses demonstrate that at non-centromeric chromosomal locations the presence of heterochromatin influences the sites at which CENP-A is incorporated into chromatin and, thus, potentially the location of centromeres.